The Relationship of Knowledge, Attitude, and Behavior to Taking Care of External Genitalia with Leucorrhea Incident in The Darul Hikmah Islamic Boarding School Student - Zahra, Khairina; Anggraini, Dwi Rita (Sumatera Medical Journal, 2020)
Introduction. Reproduction organ is one of the sensitive organ in the body and need special care. Personal hygiene habit is one of the important factor to avoid infection. It is because infection can cause vaginal discharge and cervical carcinoma. Tropical climate in Indonesia lead about 90% of girl teenagers to potentially have vaginal discharge causing bacteria, fungi, and virus easily grow. Objectives. To identify the relationship between knowledge, attitude, and behavior of taking care of external genitalia with vaginal discharge incident on students at Pondok Pesantren Modern Darul Hikmah. Methods. This is a descriptive analytical study with cross sectional design. The data was taken with primary data. Results. Leucorrhoea incidence rate at 103 respondents are 60,2% of normal vaginal discharge and 38,9% of abnormal vaginal discharge. There is a correlation between knowledge of taking care of external genitalia with vaginal discharge (p=0,001). There is correlation between attitude of taking care of external genitalia with vaginal discharge (p=0,018). There is correlation between behavior of taking care of external genitalia with vaginal discharge (p=0,002). Conclusion. There is correlation between knowledge, attitude, and behavior of taking care of external genitalia with vaginal discharge incident on students at Pondok Pesantren Modern Darul Hikmah.